(untitled) (Global Journal of Science Frontier Research, 2015)
Although fuzzy multisets or fuzzy bags are very interesting in terms of applications, it is less study or explore by researchers. Fuzzy multiset is applicable as a model of information retrieval because it has the mathematical structure or framework which expresses the number and the degree of attribution of an element simultaneously. We present a concise note on fuzzy multisets as the fuzzification or extension of multisets and the generalization of fuzzy sets. We showed the correspondence between fuzzy multisets and sequences. The Bolzano-Weierstrass property of fuzzy multisets is proposed and some theorems stated and proved.